On Stability of Logarithmic Tangent Sheaves: Symmetric and Generic Determinants. (2nd September 2021) - Faenzi, Daniele; Marchesi, Simone
Abstract: We prove stability of logarithmic tangent sheaves of singular hypersurfaces $D$ of the projective space with constraints on the dimension and degree of the singularities of $D$ . As the main application, we prove that determinants and symmetric determinants have simple (in characteristic zero, stable) logarithmic tangent sheaves and we describe an open dense piece of the associated moduli space.